Rubus chingii Hu: A Review of the Phytochemistry and Pharmacology - Yu, Guohua; Luo, Zhiqiang; Wang, Wubin; Li, Yihao; Zhou, Yating; Shi, Yuanyuan (Frontiers in Pharmacology, 2019)
Rubus chingii Hu (R. chingii), referred to as ‘‘Fu-Pen-Zi’’ in Chinese, has great medicinal and dietary values since ancient times. The dried fruits of R. chingii have been widely used in traditional Chinese medicine (TCM) for the treatment of kidney enuresis and urinary frequency for centuries. According to current findings, R. chingii has been reported to contain a variety of chemical constituents, mostly triterpenoids, diterpenoids, flavonoids and organic acids. These compounds have been demonstrated to be the major bioactive components responsible for pharmacological effects such as anticomplementary, anticancer, antioxidant, antimicrobial, and anti-inflammatory functions. Therefore, this review focused on the up-to-date published data of the literature about R. chingii and comprehensively summarized its phytochemistry, pharmacology, quality control and toxicity to provide a beneficial support to its further investigations and applications in medicines and foods.